Silences: Nature in high contrast - Chirinos, Elizabeth; Ferrer, Mireya (situArte, 2021)
Macro photography is commonly predictable and very recurrent in the theme of insects and plants, forgetting and leaving aside the amount of resources that it has and the opportunities to abstract realities, for this reason the present investigation proposes, to show the female body from a perspective far from the eroticism commonly approached. The textures of the skin and the study of the female form as a still life, serve as a source of inspiration, with the main objective of taking the nude to distance itself from familiar forms of the female body through abstraction, generating optical illusions in an expressive and dramatic way, causing ambiguities in the photographic image until reaching the viewer's optical confusion. Using the research-creation modality, the photographic series Silences: nature in high contrast is developed, composed of 30 images alluding to the absence of identities, naked nature as an art object.